2021
DOI: 10.3390/app112110483
|View full text |Cite
|
Sign up to set email alerts
|

Skull Thickness Calculation Using Thermal Analysis and Finite Elements

Abstract: In this study, the skull bone thicknesses of 150 patients ranging in age from 0 to 72 years were calculated using a novel approach (thermal analysis), and thickness changes were analyzed. Unlike conventional thickness calculation approaches (Beam Propagation, Hildebrand), a novel heat transfer-based approach was developed. Firstly, solid 3D objects with different thicknesses were modeled, and thermal analyses were performed on these models. To better understand the heat transfer of 3D object models, finite ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…In addition, noninvasive brain stimulation often tests neurophysiology in the motor circuit, with the assumption that motor-induced effects are generalizable to other brain regions such as the prefrontal cortex 66 , 67 . Prior research simulating E-fields produced by transcranial magnetic stimulation (TMS) has demonstrated that there are differences in E-field magnitude in the motor vs. prefrontal cortices 68 , which appears to be due to varying skull thicknesses and scalp-to-cortex distances between frontal, parietal, temporal, and occipital areas 69 . Therefore, future directions of our research include modeling and prospectively applying APPS-tDCS over the prefrontal and parietal cortices to determine how these principles of electrode positioning, size, and inter-electrode distance in the motor cortex might apply to different brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, noninvasive brain stimulation often tests neurophysiology in the motor circuit, with the assumption that motor-induced effects are generalizable to other brain regions such as the prefrontal cortex 66 , 67 . Prior research simulating E-fields produced by transcranial magnetic stimulation (TMS) has demonstrated that there are differences in E-field magnitude in the motor vs. prefrontal cortices 68 , which appears to be due to varying skull thicknesses and scalp-to-cortex distances between frontal, parietal, temporal, and occipital areas 69 . Therefore, future directions of our research include modeling and prospectively applying APPS-tDCS over the prefrontal and parietal cortices to determine how these principles of electrode positioning, size, and inter-electrode distance in the motor cortex might apply to different brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…34 Large animal validation studies would then take place in an animal model such as a porcine Yukatan minipig model, whose bone thickness is much greater and closer to that of humans at 10-12 mm (human skulls are 6-10 mm thick depending on exact location of the skull) as compared to rats. 35,36 At this stage, additional parameters such as diffusion of oxygen throughout the depth of the scaffold will be addressed to ensure MSC viability is maintained, possibly through the timing of MSC administration. If successful, this data will provide a promising strategy to improve bone regeneration in large bone defects that are require surgical intervention for healing.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of this study is that the scaffold dimensions (1 mm thick by 8 mm diameter) were designed in preparation for future evaluation and proof‐of‐concept, in the well‐characterized rat CMF bone defect model 34 . Large animal validation studies would then take place in an animal model such as a porcine Yukatan minipig model, whose bone thickness is much greater and closer to that of humans at 10–12 mm (human skulls are 6–10 mm thick depending on exact location of the skull) as compared to rats 35,36 . At this stage, additional parameters such as diffusion of oxygen throughout the depth of the scaffold will be addressed to ensure MSC viability is maintained, possibly through the timing of MSC administration.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning sex, we hypothesized that men would have a generally higher SCD, with smaller between-sex differences in the channels close to the vertex (McCalley and Hanlon 2021;Hanlon and McCalley 2022). We expected men to have thicker soft tissue layers, women to have thicker compact bone layers, and spongy bone, CSF, and grey matter layers to show minor-to-no differences across both sexes (Hatipoglu et al 2008;Lillie et al 2016;Anand Meundi and David 2019;Calisan et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Using GTT, we investigated sex and age differences in tissue thicknesses across different representative anatomical locations that are often recorded and stimulated using noninvasive techniques. Previous studies have shown variations in all the SCD tissues across women and men, and younger and older adults (Blatter et al 1995;Akiyama et al 1997;Kozel et al 2000;McConnell et al 2001;Makrantonaki and Zouboulis 2007;Greenberg et al 2008;Hatipoglu et al 2008;Sabancıoğulları et al 2012;Royle et al 2013;Lillie et al 2016;Ungar et al 2018;Anand Meundi and David 2019;Indahlastari et al 2020;Calisan et al 2021;McCalley and Hanlon 2021;Hanlon and McCalley 2022). However, these studies typically only investigated the effect of age or sex on a single tissue.…”
Section: Introductionmentioning
confidence: 99%